Respuesta :
If 3c+4d=2 then c=(2-4d)/3
And if you put that into the other equation
[tex] {\frac{2 - 4d}{3}}^{2} + {d}^{2} = 5[/tex]
Then you multiply everything by 3, getting
[tex] {(2 - 4d)}^{2} + 3 {d}^{2} = 15[/tex]
And then
[tex]2 - 4d + \sqrt{3} d = \sqrt{15} [/tex]
Leaving
[tex]d( \sqrt{3} - 4) = \sqrt{15} - 2[/tex]
I dont have a calc with me right now but you just pot this into the calculator:
[tex]d = \frac{ \sqrt{15} - 2 }{ \sqrt{3} - 4} [/tex]
And when you get the number you insert it into the nest eqation to get c
[tex]c = \frac{2 - 4d}{3} [/tex]
So basically
[tex]c = \frac{2 - 4 \frac{ \sqrt{15} - 2}{ \sqrt{3} - 4} }{3} [/tex]
And if you put that into the other equation
[tex] {\frac{2 - 4d}{3}}^{2} + {d}^{2} = 5[/tex]
Then you multiply everything by 3, getting
[tex] {(2 - 4d)}^{2} + 3 {d}^{2} = 15[/tex]
And then
[tex]2 - 4d + \sqrt{3} d = \sqrt{15} [/tex]
Leaving
[tex]d( \sqrt{3} - 4) = \sqrt{15} - 2[/tex]
I dont have a calc with me right now but you just pot this into the calculator:
[tex]d = \frac{ \sqrt{15} - 2 }{ \sqrt{3} - 4} [/tex]
And when you get the number you insert it into the nest eqation to get c
[tex]c = \frac{2 - 4d}{3} [/tex]
So basically
[tex]c = \frac{2 - 4 \frac{ \sqrt{15} - 2}{ \sqrt{3} - 4} }{3} [/tex]
c²+d²=5----(1)
3c+4d=2----(2)
from (2):
3c=2-4d
c=(2-4d)/3
sub c into (1):
[(2-4d)/3]² + d² =5
(16d²-16d+4)/9 + d²=5
16d²-16d +4 +9d²=45
25d²-16d+4=45
25d²-16d+4-45=0
25d²-16d-41=0
(25d-41)(d+1)=0
25d-41=0 or d+1=0
d=41/25 or d=-1
If d=41/25;
Then c=[2-4(41/25)]/3
c= 38/25
If d=-1
Then c=[2-4(-1)]/3
c=2
Answer: *c=38/25, d=41/25 or c=2, d=-1*
3c+4d=2----(2)
from (2):
3c=2-4d
c=(2-4d)/3
sub c into (1):
[(2-4d)/3]² + d² =5
(16d²-16d+4)/9 + d²=5
16d²-16d +4 +9d²=45
25d²-16d+4=45
25d²-16d+4-45=0
25d²-16d-41=0
(25d-41)(d+1)=0
25d-41=0 or d+1=0
d=41/25 or d=-1
If d=41/25;
Then c=[2-4(41/25)]/3
c= 38/25
If d=-1
Then c=[2-4(-1)]/3
c=2
Answer: *c=38/25, d=41/25 or c=2, d=-1*